Analyzing the Non-Violent Non-Cooperation Programme in Gujarat, Maharashtra and Punjab Regions of the Country: The Impact of Mahatma Gandhi's Non-Violent Non-Cooperation Programme in Gujarat, Maharashtra, and Punjab (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Mahatma Gandhi took the control of the National Movement of India in 1919 A.D. By adopting the peaceful and the constitutional methods, Mahatma Gandhi provided a new direction to the National Movement of India, on one side and on the other side, he made the National Movement of India, more self-confident Mahatma Gandhi helped the Muslims in their Khilafat Movement and he started the Non-cooperation Movement also. Non-cooperation Movement, despatched under the authority of Gandhi and the Indian National Congress was for sure that the movement has been fruitful as well as against British imperialism. The British had estimated the power and strength of Mahatma Gandhi.